The Influence of Work-Life Balance, Psychological Well-being and Work Environment on Employee Productivity - Tegar Fajar Bayhaq; Dicky Jhoansyah; Resa Nurmala (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this study was to determine whether work-life balance, psychological well-being and work environment have an influence on employee productivity at PT Bank BJB Cibadak Branch. The type of research conducted is quantitative research with a descriptive approach and associative analysis. The population and sample in this study were 30 respondents who were all employees at PT Bank BJB Cibadak Branch who used the saturated sampling technique method as sampling. The results of the research on the farsial significant test (t-test) show that work-life balance (X1) has a positive and significant effect on employee productivity (Y) seen from Thitung greater than Ttabel, namely 1.969 1.699 then H0 is rejected and H1 is accepted. psychological well-being (X2) has a positive and significant effect on employee productivity (Y) seen from Thitung greater than Ttabel, namely 191 1.699 then H0 is rejected and H1 is accepted. and the work environment shows that Thitung is greater than Ttabel, namely -1.757 1.699, so H0 is accepted and H1 is rejected, which means it can be concluded that the Work Environment (X3) has no significant effect on Employee Productivity (Y) at PT Bank BJB Cibadak Branch.